Enhancing Early Childhood Problem-Solving Abilities through Game-Based Learning and Computational Thinking: The Impact of Cognitive Styles - Ningtyas, Dhita Paranita; Setyosari, Punaji; Kuswandi, Dedi; Ulfa, Saida (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Children's understanding of solving problems related to early cognitive abilities with several levels of complexity makes children feel difficult, and students are less able to solve problems correctly according to the sequential order of how to do them. The main factor that causes low problem-solving abilities is the use of inappropriate learning strategies. So that children in the process of solving problems in a lesson also become less than optimal. This study explores the effects of computational thinking strategies with game-based learning compared to conventional approaches on early childhood problem-solving abilities, considering the cognitive styles of field-independent (FI) and field-dependent (FD) children. A quasi-experimental pretest-posttest nonequivalent control group design involved 60 children from Blitar Kindergarten. The experimental group received computational thinking instruction through game-based learning, while the control group followed conventional methods. Posttests followed a pretest established baseline abilities and an eight-week intervention. Data were analyzed using a two-way ANOVA, revealing significant improvements in problem-solving skills for the experimental group (p < 0.05). FI children outperformed FD peers, indicating cognitive style's impact on learning outcomes. An interaction effect between learning strategies and cognitive styles was identified, emphasizing the importance of tailored educational approaches. The study's findings suggest that computational thinking through game-based learning enhances critical thinking, creativity, and engagement in young learners. However, limitations such as a small sample size and short intervention duration highlight the need for further research. Future studies should involve diverse populations and longer interventions to understand the long-term effects better and optimize educational strategies for individual cognitive styles. These results underscore the potential of innovative educational methods in developing foundational skills essential for academic and life success.